2019
DOI: 10.2478/fon-2019-0042
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ experiences of caring for dying patients and their families: a systematic review and meta-synthesis

Abstract: Objective Nurses play important roles in caring for dying patients and their families. Difficulties students confronted when facing dying patients challenge the quality of nursing education. A better understanding of students’ experiences would enhance teachers’ ability in helping students. This study aims to describe available evidence about nursing students’ experiences when caring for dying patients and their families. Methods A review of qualitative studies published between 2005 and 2017 was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Nursing students understand that the families of dying patients need support. A meta-analysis review of qualitative studies describing nursing students' experiences when caring for dying patients and their families found that nursing students advocated for more caring for patients' families (Wang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students understand that the families of dying patients need support. A meta-analysis review of qualitative studies describing nursing students' experiences when caring for dying patients and their families found that nursing students advocated for more caring for patients' families (Wang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The emotional issues resulting from the death and suffering of patients are important stressors for nurses ( Lambert et al, 2004 ; Burnard et al, 2008 ). Wang (2019) conducted a systematic review of qualitative studies investigating nursing students’ experiences when caring for dying patients. The review found that students can experience a wide range of negative emotions including helplessness, feelings of incompetence, guilt, self-doubt, fear, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, supervisors and nurse tutors should also feel comfortable and prepared to approach the students and reflect on the topic together (Oliveira et al, 2016). The opportunity to share the experience with others, the guidance of a teacher or a nurse tutor with more experience in this field who can provide emotional and practical support, and the sharing of responsibilities in decision-making about end-of-life care can reduce the fear of inadequacy (Wang, 2019). One of the limitations of this study is that it only describes the reality of a higher health education institution, so it would be important to conduct it in other institutions to understand which factors can interfere with nursing students' attitudes towards death and end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…However, people are not naturally predisposed to care for someone at the end of their life, and the attitudes towards death and end-of-life care are psychological behaviors learned through social and cultural experiences (Frommelt, 1991). Considering that attitudes can be defined as a system of beliefs and knowledge that everyone has acquired or learned throughout their lives, future nurses' attitudes towards death and end-of-life care can have an important influence on the quality of the care they provide (Wang, 2019). Future professionals need to be more prepared to recognize the need and adequacy of end-of-life care.…”
Section: Introductionmentioning
confidence: 99%